2014
DOI: 10.1007/s00244-014-0090-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive and Xenobiotic Compounds in the Alien Algae Undaria pinnatifida From Argentine Patagonia

Abstract: Seaweeds have been used as food since ancient times. The edible brown algae Undaria pinnatifida is native to northeast Asia; however, in 1992, the first specimens in Patagonian environments were found and, since then, have rapidly expanded. The main object of this study was to determine, for the first time in Argentina, the nutritive composition and concentrations of trace elements and hydrocarbons in these alien algae and evaluate their usefulness as food. Sexually mature U. pinnatifida samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 43 publications
0
3
0
4
Order By: Relevance
“…With high nutritional value due to the presence of important macro‐ and micronutrients including vitamin B12, omega‐3 and ‐6 fatty acids, selenium, iodine and dietary fibre (Aguilera‐Morales et al., ; Peña‐Rodríguez et al., ; Gil et al., ), seaweeds are also studied as a source of several bioactive compounds with potential health benefits/applications (Holdt and Kraan, ; Brown et al., ). Seaweeds can also be a source of increased dietary exposure to potential harmful and persistent contaminants (such as inorganic arsenic, lead, cadmium and mercury) as well as some nutrients, such as iodine.…”
Section: Introductionmentioning
confidence: 99%
“…With high nutritional value due to the presence of important macro‐ and micronutrients including vitamin B12, omega‐3 and ‐6 fatty acids, selenium, iodine and dietary fibre (Aguilera‐Morales et al., ; Peña‐Rodríguez et al., ; Gil et al., ), seaweeds are also studied as a source of several bioactive compounds with potential health benefits/applications (Holdt and Kraan, ; Brown et al., ). Seaweeds can also be a source of increased dietary exposure to potential harmful and persistent contaminants (such as inorganic arsenic, lead, cadmium and mercury) as well as some nutrients, such as iodine.…”
Section: Introductionmentioning
confidence: 99%
“…In VP, relatively high concentrations of Cu, Mn and Cr were detected, especially at station 8. Previous studies on trace metals in different matrices, such as sediments, seston, algae, invertebrates and marine mammals, are available for the San José Gulf and Nuevo Gulf (Harvey and Gil 1988;Gil et al 1989Gil et al , 2015Rosas et al 2012;Giarratano et al 2014) but not for the external zone of the peninsula. In the present study, it was considered that there is a tidal mixing front in VP, a thermal front observed in spring and summer, that defines the boundary between stratified (offshore) waters and a coastal, vertically mixed body of water which could have an effect on the fraction of the particulate metals.…”
Section: Discussionmentioning
confidence: 99%
“…Keberadaan lebih dari 200 campuran ekstrak rumput laut di pasar sebagian besar karena variasi dalam kombinasi dan konsentrasinya, dan pada berbagai fungsi yang diinginkan (Whistler & BeMiller, 1993). Nilai Gizi yang tinggi yang dimiliki oleh rumput laut karena adanya makro dan mikronutrien penting termasuk vitamin B12, asam lemak omega-3 dan -6, selenium, yodium dan serat makanan (Morales, Valdez, inguez, Acosta & Gil, 2005;Rodriguez, Mawhinney, Marie & Suarez, 2011;Gil, Torres, Commendatore, Marinho, Arias, Giarratano & Casas, 2015), rumput laut juga dipelajari sebagai sumber dari beberapa senyawa bioaktif dengan manfaat pada aplikasi kesehatan potensial (Holdt & Kraan. 2011;Brown, Allsopp, Magee, Gill, Nitecki, Strain & McSorley, 2014).…”
Section: Pendahuluanunclassified